The thorny complexities of visualization research for clinical settings: A case study from genomics - Ståhlbom, Emilia; Molin, Jesper; Ynnerman, Anders; Lundström, Claes (Frontiers in Bioinformatics, 2023)
In this perspective article we discuss a certain type of research on visualization for bioinformatics data, namely, methods targeting clinical use. We argue that in this subarea additional complex challenges come into play, particularly so in genomics. We here describe four such challenge areas, elicited from a domain characterization effort in clinical genomics. We also list opportunities for visualization research to address clinical challenges in genomics that were uncovered in the case study. The findings are shown to have parallels with experiences from the diagnostic imaging domain.